2004
DOI: 10.1073/pnas.0400163101
|View full text |Cite|
|
Sign up to set email alerts
|

CK2 phosphorylation of CCA1 is necessary for its circadian oscillator function in Arabidopsis

Abstract: The circadian clock controls numerous physiological and molecular processes in organisms ranging from fungi to human. In plants, these processes include leaf movement, stomata opening, and expression of a large number of genes. At the core of the circadian clock, the central oscillator consists of a negative autoregulatory feedback loop that is coordinated with the daily environmental changes, and that generates the circadian rhythms of the overt processes. Phosphorylation of some of the central oscillator pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
138
0
3

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(147 citation statements)
references
References 47 publications
6
138
0
3
Order By: Relevance
“…Surprisingly, we were unable to detect any monomers or heterodimers of CCA1 and LHY. CCA1 and LHY monomers are predicted to be 67 and 70 kD, respectively, but migrate at 75 and 80 kD, respectively, when subject to electrophoresis in denaturing conditions Daniel et al, 2004). We found that both CCA1 and LHY are present in a large complex (.440 kD; Fig.…”
Section: Cca1 and Lhy Are Found In A Large Complexmentioning
confidence: 68%
See 1 more Smart Citation
“…Surprisingly, we were unable to detect any monomers or heterodimers of CCA1 and LHY. CCA1 and LHY monomers are predicted to be 67 and 70 kD, respectively, but migrate at 75 and 80 kD, respectively, when subject to electrophoresis in denaturing conditions Daniel et al, 2004). We found that both CCA1 and LHY are present in a large complex (.440 kD; Fig.…”
Section: Cca1 and Lhy Are Found In A Large Complexmentioning
confidence: 68%
“…The immunoprecipitation was performed as described by Shalitin et al (2002) using either anti-GFP (sc-8334; Santa Cruz Biotechnology) or anti-LHY antibody (Daniel et al, 2004). Immunoblotting was performed as described (Lu and Hrabak, 2002) with the appropriate primary antibody (affinity-purified anti-CCA1 antibody; Wang and Tobin, 1998), affinitypurified anti-LHY antibody (Daniel et al, 2004), anti-GFP (sc-8334; Santa Cruz Biotechnology), anti-MYC (Upstate), or anti-HA (Abcam).…”
Section: Protein Analysis and Coimmunoprecipitationmentioning
confidence: 99%
“…4B). Although the only demonstrated targets of CK2 are CCA1 and LHY (Sugano et al, 1998(Sugano et al, , 1999Daniel et al, 2004), the additive nature of the reduction of these three CKBs suggests that they all contribute similarly to the control of CCA1 and LHY activity, and/or that the activity of other clock components are also affected. The latter case is very likely since ectopic expression of CCA1 or LHY, or loss-of-function CCA1/ LHY alleles result in arrhythmicity or period shortening, respectively.…”
Section: Functional Tools Of Reverse Genetic Studies Using Amirna In mentioning
confidence: 99%
“…The phosphorylation of CCA1, mediated at least in part by CK2, is required for its function. 53,54 A circadian phosphorylation pattern has also been in the alternative splicing of PRR7 and PRR9 partially contribute to lengthening of the circadian period in the skip-1 mutant. 92 STIPL1 is a homolog of the spliceosomal proteins TUFTELIN-INTERACTING PROTEIN11 (TFIP11) in humans and Ntr1p in yeast, which are involved in spliceosome disassembly.…”
Section: Fine-tuning Of Protein Activity and Degradation In The Circamentioning
confidence: 99%
“…15,54 The homodimerization and heterodimerization of CCA1α and LHY are important for the ability of these proteins to regulate circadian rhythms. 54,81,82 The splice variant CCA1β represses CCA1α and LHY activity by competitively forming nonfunctional CCA1α/CCA1β and CCA1β/LHY heterodimers, creating a self-regulatory circuit for CCA1 and LHY through the alternative splicing of CCA1. 80 Thus, transcription factors can auto-regulate their expression by generating competitive inhibitors through alternative splicing.…”
Section: Acknowledgmentsmentioning
confidence: 99%